The Effect of Learning Interest and Discipline on Students' PAI Learning Outcomes at MTs Terpuda Nurul Qodiri - Khabib Choiriah; Agus Setiawan; Dedi Setiawan (Assyfa Journal of Multidisciplinary Education, 2026)
This study aims to analyze the influence of learning interest and discipline on students' PAI (Islamic Religious Education) learning outcomes at MTs Terpadu Nurul Qodiri Lempuyang Bandar, Way Pengubuan, Central Lampung. Learning interest and discipline are internal and behavioral factors that play a crucial role in determining academic achievement. This research employed a quantitative approach with a correlational design. The population consisted of all students at MTs Terpadu Nurul Qodiri Lempuyang Bandar, totaling 195 students, with a sample of 49 respondents selected using proportional stratified random sampling. Data were collected through questionnaires, observation, tests, and documentation. The instruments were validated using Aiken's V and tested for reliability using Cronbach's Alpha. Data analysis techniques included multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²). The findings reveal that learning interest significantly influences PAI learning outcomes, with a t-count value of 3.815 > t-table 1.678 and a significance value of 0.000 < 0.05. Discipline also significantly influences PAI learning outcomes, with a t-count value of 3.191 > t-table 1.678 and a significance value of 0.003 < 0.05. Simultaneously, both learning interest and discipline significantly influence PAI learning outcomes, with an F-count value of 14.276 > F-table 3.20 and a significance value of 0.000 < 0.05. The coefficient of determination (R²) shows that both variables contribute 38.3% to PAI learning outcomes, while the remaining 61.7% is influenced by other factors. This study concludes that higher learning interest and discipline lead to better PAI learning outcomes. The implications of this research emphasize the importance of developing learning interest and discipline to enhance student achievement in Islamic Religious Education.